A Comparative Study of Kinetics of HCl and HClO4 Acid Catalyzed Oxidation of 2-Butanone by Selenium Dioxide in Aqueous Acetic Acid Medium - Shrivastava, Anshu; Tiwari, Sanjay; Tiwari, K.S.; Tiwari, B.M.L. (Asian Journal of Chemistry, 2016)
Hydrochloric and perchloric acid catayzed oxidation of 2-butanone by selenium dioxide has been studied in 70% aqueous acetic acid medium. The reactions show first order dependence in oxidant [SeO2]. The order of reaction with respect to substrate, hydrochloric acid and perchloric acid is one. Effect of dielectric constant of medium and effect of neutral salt has also been investigated. Various thermodynamic parameters have also been evaluated. End products have been identified as 2,3-diketone. A probable mechanism has been suggested on the basis of experimental results of both acids.